KEPEDULIAN ORANG TUA TERHADAP HASIL BELAJAR DAN PEMBINAAN AKHLAK ANAK DI MTsS YAPENA ARUN - Hadi Aditya, Abdul; Nurhayati, Nurhayati; Nurlaila, Nurlaila (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
Parents' Concern for Learning Outcomes and Moral Development of Children at Mtss Yapena Arun is the title of this study. The purpose of this study is to characterize the ways in which parents at MTsS Yapena Arun are concerned about their children's moral growth and academic performance, as well as to identify the barriers to this concern. This qualitative study uses a case study methodology to investigate how parents are concerned with their children's moral development and academic performance. The parents of students at MTsS Yapena Arun serve as the primary source of data for this study. techniques for gathering data through documentation, interviews, and observation. Condensing, presenting, and making conclusions are all part of the data analysis technique. The findings of the study indicate that: First, parents can be concerned about learning outcomes in three different ways: by offering facilities, by offering direction, and by offering counsel and encouragement. Second, there are three ways that parents can support their children's moral development: setting a good example, teaching them to do good deeds, and using incentives and penalties. Third, the social context and unrestrained smartphone use are factors that prevent parents from recognizing concerns. ABSTRAK Penelitian ini berjudul Kepedulian Orang Tua Terhadap Hasil Belajar Dan Pembinaan Akhlak Anak Di Mtss Yapena Arun. Tujuan penelitian ini adalah mendeskripsikan bentuk kepedulian orang tua terhadap hasil belajar dan pembinaan akhlak anak di MTsS Yapena Arun. Penelitian ini merupakan penelitian kualitatif dengan pendekatan studi kasus, guna menemukan bentuk kepedulian orang tua terhadap hasil belajar dan pembinaan akhlak anak. Sumber data utama penelitian ini adalah orang tua siswa di MTsS Yapena Arun. Metode pengumpulan data melalui observasi, wawancara, dan dokumentasi. Metode analisis data menggunakan kondensasi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: Pertama. Bentuk kepedulian orang tua terhadap hasil belajar ada tiga, yaitu memberikan fasilitas, memberikan bimbingan, dan memberikan nasihat dan motivasi. Kedua. Bentuk kepedulian orang tua terhadap pembinaan akhlak ada tiga, yaitu menjadi teladan yang baik, membiasakan anak melakukan hal yang baik, dan memberikan hadiah dan hukuman.